A comparison of risk scores' long-term predictive abilities for patients diagnosed with ST elevation myocardial infarction who underwent early percutaneous coronary intervention. (31st December 2022) - Aldujeli, Ali; Haq, Ayman; Hamadeh, Anas; Stalmokaite, Auguste; Maciulevicius, Laurynas; Labanauskaite, Egle; Navickaite, Inesa; Kurnickaite, Zemyna; Jarusevicius, Gediminas; Unikas, Ramunas; Zaliaduonyte, Diana; Tecson, Kristen M.
Abstract: Objective . To compare the long-term (5 year) prognostic values of commonly used risk scores on major adverse cardiovascular events (MACE) in a cohort of patients who underwent primary PCI for STEMI. Design . We created a composite endpoint of MACE, defined as the occurrence of any of the following events within 5 years: ischemic or hemorrhagic stroke, target vessel revascularization, nonfatal myocardial infarction, cardiovascular death. We dichotomized risk scores into high risk and not high risk according to the literature's pre-existing cutoffs as follows: GRACE score >127 = high risk, SYNTAX I score ≥33 = high risk, SYNTAX II ≥32 high risk, TIMI >8 = high risk. We utilized the area under the receiver operating characteristic curve (AUC) as the metric for predictive ability. Results . There were 768 patients in this study and 416 (54.2%), 209 (27.2%), 511 (66.5%), and 74 (9.6%) were at high risk according to the GRACE, SYNTAX I, SYNTAX II, and TIMI scores, respectively. The AUCs for 5-year MACE were 0.54 (95% confidence interval (CI): 0.49–0.59, p  = .0947), 0.79 (95% CI: 0.75–0.83, p  < .0001), 0.58 (95% CI: 0.54–0.62, p  = .0004), and 0.5 (95% CI: 0.48–0.53, p  = .7259), respectively. Conclusion . SYNTAX I score was superior in predicting MACE in patients with STEMI and a high burden of CAD. Utilizing the basal SYNTAX I score in STEMI patients with significant non-culprit CAD may improve risk stratification, decision-making, and outcomes.